Phonetic Methods on The Early Reading Ability of Student with Intellectual Disability - Nuri Hidayati; Asep Sunandar; Rizqi Fajar Pradipta (Universitas Negeri Malang, 2020)
Abstract: Influence phonetic method the Early Reading Ability of Intellectual Student with a disability. The study aims to determine the influence of the phonetic method on the Early Reading Ability of Students with Intellectual a disability. The research is a quantitative research approach to Single Subject Research (SSR). The results of the study indicate that there is an influence on the phonetic method of the Early Reading Ability of Students with Intellectual Disability